Managing Spaghetti Syndrome with a Prototype IV Pole Hook: A Nursing Perspective - Balmeo, Jhonee (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the perceived effectiveness and usability of the Prototype IV Pole Hook in managing IV-related Spaghetti Syndrome among nurses in hospital settings in Cabanatuan City, Nueva Ecija. Guided by Everett Rogers’ Five Factors of Diffusion of Innovation Theory and product usability measures, the study used a descriptive correlational research design. The respondents were 114 registered nurses with at least three years of clinical experience and direct involvement in IV line management. After using the prototype for approximately one to two weeks, the nurses assessed its perceived effectiveness in terms of relative advantage, compatibility, complexity, trialability, and observability, and its usability in terms of novelty, technical merit, and system usability. Findings showed that the Prototype IV Pole Hook was rated at a high level across all innovation attributes, indicating that it was perceived as useful, compatible with nursing routines, easy to use, testable, and visibly beneficial in organizing multiple IV lines. It also obtained high ratings in novelty, technical merit, and system usability, suggesting that the device was viewed as innovative, technically sound, and user-friendly. Demographic profile had no significant relationship with perceived effectiveness, while perceived effectiveness had significant positive relationships with usability. The study concluded that the prototype has potential to support safer and more efficient IV line management, although further design improvement, broader testing, and longer trial periods were recommended. The study aligns with SDG 3, SDG 8, and SDG 9 by promoting patient safety, safer nursing work, and practical healthcare innovation. Its sustainability impact lies in supporting public health, institutional improvement, nursing workflow efficiency, and locally relevant medical device development.
Keywords: Cabanatuan City; Diffusion of Innovation Theory; IV Line Management; Nurses; Patient Safety; Product Usability; Prototype IV Pole Hook; Spaghetti Syndrome; System Usability